Geographical Variation in Medication Prescriptions: A Multiregional Drug-Utilization Study - Russo, Veronica; Orlando, Valentina; Monetti, Valeria Marina; Galimberti, Federica; Casula, Manuela; Olmastroni, Elena; Tragni, Elena; Menditto, Enrica; , EDU.RE.DRUG Group; Catapanoa, Alberico L.; Tragni, Elena; Menditto, Enrica; et al. (Frontiers in Pharmacology, 2020)
Background: Studies have emphasised the importance of geographical factors and general practitioner (GP) characteristics in influencing drug prescriptions. Objectives: To: (i) ascertain the prevalence rate (PR) of use of drugs in six therapeutic categories used for chronic conditions; (ii) assess how geographical characteristics and GP characteristics may influence drug prescribing. Methods: This study is part of the EDU.RE.DRUG Project, a national collaborative project founded by Italian Medicine Agency (AIFA). Cross-sectional analyses were undertaken employing the pharmacy-claim databases of four local health units (LHUs) located in two Italian regions: Lombardy and Campania. Six drug categories were evaluated: proton-pump inhibitors; antibiotics; respiratory-system drugs; statins; agents acting on the renin−angiotensin system; psychoanaleptic drugs. The PR was estimated according to drug categories at the LHU level. A linear multivariate regression analysis was undertaken to evaluate the association between the PR and geographical area, age and sex of GPs, number of patients, and percentage of patients aged >65 per GP. Results: LHUs in Campania showed a PR that was significantly higher than that in Lombardy. Antibiotics showed the highest PR in all the LHUs assessed, ranging from 32.5% in Lecco (Lombardy) to 59.7% in Naples-2 (Campania). Multivariate linear regression analysis confirmed the association of the PR with geographical area for all drug categories. Being located in Campania increased the possibility of receiving a drug prescription from the categories considered, with estimates more marked for antibiotics, proton-pump-inhibitors, and respiratory-system drugs. Conclusions: This study provides information about the PR of medications used for treating common and costly conditions in Italy and highlighted a significant geographical variation. These insights could help to develop area-specific strategies to optimise prescribing behaviour.